THE OCCURRENCE DURING ACUTE INFECTIONS OF A PROTEIN NOT NORMALLY PRESENT IN THE BLOOD : I. DISTRIBUTION OF THE REACTIVE PROTEIN IN PATIENTS' SERA AND THE EFFECT OF CALCIUM ON THE FLOCCULATION REACTION WITH C POLYSACCHARIDE OF PNEUMOCOCCUS - Abernethy, Theodore J. (The Rockefeller University Press, 1941)
The serum obtained from human beings and monkeys during the acute phase of diverse infections contains a protein which is precipitable by the C polysaccharide of pneumococcus. The distribution of this protein in acute phase serum has been studied, and the effect of calcium on the precipitation reaction with the C polysaccharide is described. Other distinctive features of this reaction are discussed. 1. When heated above 65°C., serum obtained from patients during certain acute infections loses the property of reacting in precipitation tests with the C polysaccharide of pneumococcus. The loss of activity under these conditions occurs at temperatures known to denature many proteins. 2. The reactive component in "acute phase" serum which precipitates with the C polysaccharide is tentatively regarded as a protein. 3. The reactive substance is associated with the albumin fraction of serum. 4. In the reaction between patients' serum and C polysaccharide, flocculation is conditioned by the presence of calcium ions. 5. The following distinctive features of the C-reaction are discussed with reference to known characteristics of antigen-antibody phenomena: (a) the occurrence of the reactive component in blood only during the acute stage of the infection; (b) the lack of specificity of the reaction with respect to the inciting cause of the disease; (c) the presence of the active substance in the albumin fraction of the serum; (d) the action of calcium in producing flocculation.